Sleep habits of young football players: can the weekend off help catch up from sleep debt? - Barreira, J.; Brito, J.; Nakamura, F.; Figueiredo, P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sleep is essential for the health and well-being of all individuals. However, the younger population appears more vulnerable to short sleep durations, most likely due to a combination of biological, psychosocial, and societal pressures that come together and compete with one another affecting sleep [1]. Thus, it is common for teenagers to adjust their sleep schedules during the weekends to "catch up" on their sleep debt from weekdays [2, 3]; however, this might not be possible for young football players since they play official matches on the weekends during the competitive period. METHODS: Twenty-three highly trained young football players (mean ± SD; age: 17.3 ± 0.6 yrs) from the same U19 team were recruited. Sleep was objectively monitored using actigraphy devices for eight weeks, comprising two types of microcycles: normal (i.e., with an official match on the weekend) and off (i.e., with a weekend off, without matches). Linear mixed models were used to analyze the differences in sleep variables between microcycle type (normal vs. off) and night-type (weekday vs. weekend). Significance was set at p